Relações familiares no contexto da guarda compartilhada: a perspectiva dos filhos adolescentes - Fiorot, Larissa Alves (2023)
It is understood that the shared custody modality was designed with the purpose of ensuring the children's right to coexistence with both caregivers, and reducing the impacts that divorce can have on the children's development. In this sense, it is important to reflect on family relationships in the context of shared custody, giving the subject a voice, considering how the children perceive this experience. In this way, this research aimed to understand the repercussions of divorce for teenage children and It is understood that the shared custody modality was concieved with the purpose of ensuring the children's right to coexistence with both caregivers, and of reducing the impacts that divorce can have on the children's development. In this sense, it is important to think about family relationships in the context of shared custody, giving the subject a voice, considering how the children understand this experience. Thus, this research aimed to understand the repercussions of divorce for teenage children and investigate family dynamics and relationships between parents and teenage children in shared custody. Seeking to meet the proposed objective, which encompasses the perceptions of adolescents regarding their family environment, this research used a qualitative methodology. Four adolescents who lived in shared custody participated in this study. For data collection, the following instruments were used: interview with a semi-structured script, affective map and diary technique. As a procedure for data analysis, thematic analysis was used. The research was substantiated and discussed based on the Bioecological Theory of Human Development (TBDH), proposed by Urie Bronfenbrenner. As main results, it was found that even under shared custody, the mother was recognized by the children as the main parental guardian. Cohabitation was found to be associated with the father's level of participation in the child's life, since only the teenager with a shared residence indicated the father figure exercising the same degree of responsibility as the mother figure. It was observed that, although parents did not carry out major responsibility activities, they were still present and cultivating relationships with their children. Thus, it is concluded that, when compared to other regimes, shared custody enables greater parental involvement of both caregivers in the lives of their adolescent children.